Design and Optimization of Isopropyl Alcohol-Water Separation using Heterogenous Azeotropic Distillation - Emelia Kezia Lasut; Yansen Hartanto; Herry Santoso (CHEMICA: Jurnal Teknik Kimia, 2021)
Heterogeneous azeotropic distillation is one technique of separating the mixtures that form azeotropes. In this research, a case study will be carried out on separating a mixture of isopropyl alcohol (IPA) and water where this mixture forms an azeotropic point. IPA is an alcohol that can be converted into diesel fuel through an esterification reaction. This study will use the Aspen Plus v8.8 simulator. The entrainer used were benzene and cyclohexane. The thermodynamic model used was NRTL. The configuration used in this study consists of two distillation columns with one decanter to separate the ternary azeotropic points. Optimization is carried out sequentially by changing one variable while the other variables are kept constant. The variables used are the number of stages, and the location of the feed entered in each column. The objective function used in this optimization is the Total Annual Cost (TAC). This research obtained a heterogeneous azeotropic distillation configuration that produced high-purity IPA and water products. Based on the optimization results, the benzene entrainer is cheaper than the cyclohexane entrainer.